PENERAPAN MODEL PEMBELAJARAN KOOPERATIFPENDEKATAN STRUKTURAL TEAM PAIR SOLO UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII.3 SMP NEGERI 6PEKANBARU - Machdalena Ilyasya Ilyasya; Susda Heleni Heleni; Sehatta Saragih Saragih (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research aims to improve learning process in order to increase mathematics learning outcomes in SMP Negeri 6 Pekanbaru by implementing cooperative learning model of Team Pair Solo structural approach to mathematics lesson. Subjects of the research were studentsgrade VIII.3whohave theacademicability oftheheterogeneous. This research is aclassroomaction research with twocycles. Each cyclehas fourstages, thestagesareplanning, action, observationandreflection. The results showed the activity of teachers and students have done well after doing the action. An increase in the number of students who achieved at UH KKM end of each cycle compared to the number of students who achieve KKM on base score.The result of study in the first cycle found that the percentage of students who achieve KKM is75,00% and the second cycle is 82,14%, an increase from before the measures the percentage is only 28,57%. Results of this research indicate that theimplementing of cooperative learning model for Team Pair Solo structural approachcanimprove mathematics learning processand increase outcomes of students grade VIII.3 SMP Negeri 6 Pekanbaru in the second semester academic year2013/2014. Keywords: Mathematics learning outcome, Cooperative learning, Team Pair Solo, Classroom action research.